Machine intelligence in peptide therapeutics: A next‐generation tool for rapid disease screening. Issue 4 (10th January 2020) - Basith, Shaherin; Manavalan, Balachandran; Hwan Shin, Tae; Lee, Gwang
Abstract: Discovery and development of biopeptides are time‐consuming, laborious, and dependent on various factors. Data‐driven computational methods, especially machine learning (ML) approach, can rapidly and efficiently predict the utility of therapeutic peptides. ML methods offer an array of tools that can accelerate and enhance decision making and discovery for well‐defined queries with ample and sophisticated data quality. Various ML approaches, such as support vector machines, random forest, extremely randomized tree, and more recently deep learning methods, are useful in peptide‐based drug discovery. These approaches leverage the peptide data sets, created via high‐throughput sequencing and computational methods, and enable the prediction of functional peptides with increased levels of accuracy. The use of ML approaches in the development of peptide‐based therapeutics is relatively recent; however, these techniques are already revolutionizing protein research by unraveling their novel therapeutic peptide functions. In this review, we discuss several ML‐based state‐of‐the‐art peptide‐prediction tools and compare these methods in terms of their algorithms, feature encodings, prediction scores, evaluation methodologies, and software utilities. We also assessed the prediction performance of these methods using well‐constructed independent data sets. In addition, we discuss the common pitfalls and challenges of using ML approaches for peptide therapeutics. Overall, we show that using ML models in peptide research can streamline the development of targeted peptide therapies.